IIUM integrated design project framework for SDG innovation - Ramli, Nabilah; Wan Nordin, Mimi Aminah (2019)
IIUM Integrated Design Project framework for SDG Innovation is an education framework designed to nurture technopreneurial mindset in engineering students through pragmatic capstone project within regional industrial context. This framework will be the funnel of innovative technopreneurs for IIUM startup ecosystem for successful spin-off potentials in 3 identified key industries: renewable energy, affordable healthcare and smart agriculture. This framework aims to build the right kind of innovation driver capacities that can be achieved through a proper alignment of education structure that requires synergistic involvements from the identified industries, entrepreneurs, relevant policy makers, students and well trained faculty members.